PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Sonya Nova Anggini Supranda; Indra Prasetyo; Woro Utari (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
The purpose of this study was to describe compensation, organizational culture, work motivation and performance of employees of the Meranti Islands District DPRD Office. To analyze the effect of compensation and organizational culture on the performance of employees of the Meranti Islands District DPRD Office through work motivation. This research was carried out at the Meranti Islands Regency DPRD Office with a population of 37 people, then the sample used was all members of the population used as samples, namely all employees of the Meranti Islands Regency DPRD, totaling 37 people. The sampling technique used is total sampling. This study uses data analysis techniques Descriptive Statistical Test and hypothesis testing with Structural Equation Modeling (SEM), using Partial Least Square (PLS). The results showed that compensation, organizational culture, work motivation of DPRD Meranti Islands Regency employees were in the high category while the performance of DPRD Meranti Islands Regency employees was in a very high category. Compensation had no significant effect on motivation, Organizational culture had no significant effect on motivation, Compensation had an effect with a significant effect on performance, organizational culture has a significant effect on performance, work motivation has a significant effect on performance, work motivation can mediate compensation has no significant effect on performance, work motivation can mediate organizational culture with a significant effect on performance.